Radiogenic Heat Variation with Lithology in Clastic Sediments Deduced from Well Logs. An implication for Hydrocarbon Generation: ATG-Field, Niger Delta Basin - Sebastian Abraham Sunu; Lucky Peter Kenda; Adetola Sunday Oniku; Osita Chukwuemeka Meludu; Abbey Chukwuemeka Patrick; Joseph Aza Ahile (Geological Engineering Department Universitas Gadjah Mada, 2025)
This study investigates the variation of Radiogenic heat production (RHP) from four sets of wells logs namely ATG-10, ATG-11, ATG-7, and ATG-5 recorded in clastic sediments of Benin, Agbada and Akata formations in ATG field shallow offshore Niger Delta. Major lithology observed in the gamma ray log was sand, shale and shale-sand intercalations. The variations of radiogenic heat production (RHP) were computed using the total gamma ray count (GR) combined with density logs (RHOB) using the Bucker and Rybach linear methods. Heat production rates calculated was found to vary from 0.23-2.24 µWm-3 ± 0.08 for ATG 10, and 0.22-2.25 µWm-3 ± 0.08 for ATG 11, then 0.31- 2.35 µWm-3± 0.08 for ATG 7 and 0.34-2.33 µWm-3 ± 0.08 for ATG 5. The average radiogenic heat production ranges between 0.9 µWm-3- 2.29 µWm-3. It was observed that high values of radiogenic heat production were in the shale lithology of the Akata formation, and this was as a result of high concentration of radioelements (uranium, Thorium and Potassium) in the sediment. And low values of RHP in sand lithology in the Benin formation and it was as a result of low concentrations of radio elements. The magnitudes of RHP calculated in this study can produce enough heat which may have an effect on the hydrocarbon potential in the clastic sediments of the Niger Delta and also may classify thermal regime and also contributes to the maturation of Kerogen into hydrocarbon in the Niger Delta. Depth versus RHP cross plots showed heat production tends to increase with depth since the basin is underlain by Akata formation and is mainly marine shales. Where spectral gamma ray data are not available, the relationship between RHP Gamma ray and density log established in this study may be used in any part of the Niger Delta to calculate RHP.